INFORMATION SYSTEM DESIGN PROCUREMENT OF GOODS AND SERVICES PT. UNITEKNINDO CORE MEANS USING MICROSOFT ACCESS - Sukirmawati Sukirmawati; Sutarno Sutarno, Skom, MMSi (Jurnal Sistem Informasi, 2005)
PT. UNITEKNINDO CORE MEANS is a company specialized is engaged in theoperation and maintenance of the building (Building Operations & MaintenanceServices / BOMS).One supporter in the implementation of building maintenance undertaken PT. COREFACILITIES UNITEKNINDO is procurement system.Relating to these premises, the authors are interested in creating a procurementsystem for goods and services at PT. UNITEKNINDO CORE MEANS. Unit laboremployment PLN headquarters by using the application program Microsoft Access.